Tantangan ALKI dalam Mewujudkan Cita‐cita Indonesia sebagai Poros Maritim Dunia - Ismah Rustam (Universitas Diponegoro, 2016)
Making Indonesia the worldʹs maritime axis is the vision promoted by Joko Widodo(Jokowi) to the next five years of his tenure after his victory in the presidential election 2014. Thisgoal is in line with the struggle of Sukarno, who wanted Indonesia to become a strong andindependent maritime country at the time. His desire was rooted from the awareness of Indonesia’sstrategic position as well as maritime potentials that the country have. The main objective ofJokowi’s idea is to boost Indonesiaʹs economic growth and equitable development which is focusedon the marine sector. The development of maritime force is not without obstacles. The policy tobuild Indonesian Archipelagic Sea Lanes (ALKI) makes Indonesia as an ‘open country’. Untilnow, a wide range of foreign shipping and airlines are freely passing cut of Indonesia. Securitythreats on three ALKI lines would become the challenge for the Indonesian government towardsthe maritime axis.Keywords: maritime axis, ALKI, Indonesia